Direct anterior approach (DAA) vs. conventional approaches in total hip arthroplasty: A RCT meta-analysis with an overview of related meta-analyses. - Philip Lazaru; Simon Bueschges; Nikolai Ramadanov (PLoS ONE)
Objectives Several systematic reviews and meta-analyses on short-term outcomes between total hip arthroplasty (THA) through direct anterior approach (DAA) compared to THA through conventional (including anterior, anterolateral, lateral transgluteal, lateral transtrochanteric, posterior, and posterolateral) approaches (CAs) in treatment of hip diseases and fractures showed contradicting conclusions. Our aim was to draw definitive conclusions by conducting both a fixed and random model meta-analysis of quality randomized controlled trials (RCTs) and by comparison with related meta-analyses. Design We performed a systematic literature search up to May 2020 to identify RCTs, comparing THA through DAA with THA through CAs and related meta-analyses. We conducted risk of bias and level of evidence assessment in accordance with the Cochrane's Risk of Bias 2 tool and with the guidelines of the Centre for Evidence-Based Medicine. We estimated mean differences (MD) with 95% confidence intervals (CI) through fixed and random effects models, using the DerSimonian and Laird method. Heterogeneity was assessed using tau-square (τ2). Our conclusions take into account the overall results from related meta-analyses. Results Nine studies on THA through DAA met the criteria for final meta-analysis, involving 998 patients. Three studies were blinded RCTs with a level I evidence, the other 6 studies were non-blinded RCTs with a level II evidence. We came to the following results for THA through DAA compared to THA through CAs: operation time (I2 = 92%, p<0.01; fixed: MD = 15.1, 95% CI 13.1 to 17.1; random: MD = 18.1, 95% CI 8.6 to 27.5); incision length (I2 = 100%, p<0.01; fixed: MD = -2.9, 95% CI -3.0 to -2.8; MD = -1.1, 95% CI -4.3 to 2.0); intraoperative blood loss (I2 = 87%, p<0.01; fixed: MD = 51.5, 95% CI 34.1 to 68.8; random: MD = 51.9, 95% CI -89.8 to 193.5); VAS 1 day postoperatively (I2 = 79%, p = 0.03; fixed: MD = -0.8, 95% CI -1.2 to -0.4; random: MD = -0.9, 95% CI -2.0 to 0.15); HHS 3 months postoperatively (I2 = 52%, p = 0.08; fixed: MD = 2.8, 95% CI 1.1 to 4.6; random: MD = 3.0, 95% CI -0.5 to 6.5); HHS 6 months postoperatively (I2 = 0%, p = 0.67; fixed: MD = 0.9, 95% CI -1.1 to 2.9; random: MD = 0.9, 95% CI -1.1 to 2.9); HHS 12 months postoperatively (I2 = 0%, p = 0.79; fixed: MD = 0.7, 95% CI -0.9 to 2.4; random: MD = 0.7, 95% CI -0.9 to 2.4). We compared our findings with 7 related meta-analyses. Conclusions Considering the results of our meta-analysis and the review of related meta-analyses, we can conclude that short-term outcomes of THA through DAA were overall better than THA through CAs. THA through DAA had a shorter incision length, a tendency towards a lower pain VAS 1 day postoperatively and better early postoperative functional outcome than THA through CAs. The intraoperative blood loss showed indifferent results. THA through DAA had a longer operation time than THA through CAs.